Reflections on the NCS to NCS (CAPS): Foundation Phase teachers’ experiences - Du Plessis, Elize; Marais, Petro (The IIE, 2015)
The Curriculum and Assessment Policy Statement (CAPS) is a modification of what to teach (curriculum) and not how to teach (teaching methods) in South African schools. In July 2009, the Minister of Basic Education appointed a panel of experts (an independently constituted quality assurance body) to investigate the nature of the challenges and problems experienced in the implementation of the National Curriculum Statement (NCS). During 2011 the NCS was reviewed extensively; amendments were made to the NCS, which is now referred to as the NCS (CAPS). The aim of this study was to evaluate whether or not the amended NCS (CAPS) is an improvement on the original NCS. The Reflective Model of Gibbs and the Appreciative Inquiry Theory were used as theoretical frameworks. A qualitative research approach was used and 16 Foundation Phase teachers were interviewed to determine their views on the differences between the NCS and the NCS (CAPS). The main results indicated that implementation of the amended NCS (CAPS) remains a challenge.
Keywords: Teaching Methods; Foundation Phase Teaching; CAPS; The Reflective Model of Gibbs; The Appreciative Inquiry Theory; Qualitative research